Association between Mediterranean lifestyle and perception of well-being and distress in a sample population of university Italian students - Quarta, S. (2023)
We investigated the extent to which adherence to the Mediterranean diet (MD) in combination with Mediterranean lifestyle factors influenced students’ perceptions of subjective well-being (SWB) and distress. 939 undergraduates completed a survey to assess sociodemographic and lifestyle characteristics, including adherence to the MD, depression, anxiety, stress, and SWB. Data were analysed with correlation, logistic, and multiple linear regression models. Higher adherence to MD correlated with better SWB. Fruit, red meat, sweet and caffeinated beverages contributed significantly. However, it was the combination of adherence to MD with other factors, including quality of social relationships, income, smoking, sleep, and physical activity that better predicted SWB. Our results confirm the positive influence of MD on SWB. However, they also suggest the need to consider perceptions of well-being by a more holistic approach that considers physical and social factors simultaneously to improve the development of more effective educational and motivational programmes.